The Arabidopsis ATR-SOG1 signaling module regulates pleiotropic developmental adjustments in response to 3'-blocked DNA repair intermediates. Issue 2 (15th November 2021) - Li, Jinchao; Liang, Wenjie; Liu, Yi; Ren, Zhitong; Ci, Dong; Chang, Jinjie; Qian, Weiqiang
Abstract: Base excision repair and active DNA demethylation produce repair intermediates with DNA molecules blocked at the 3′-OH end by an aldehyde or phosphate group. However, both the physiological consequences of these accumulated single-strand DNAs break with 3′-blocked ends (DNA 3′-blocks) and the signaling pathways responding to unrepaired DNA 3′-blocks remain unclear in plants. Here, we investigated the effects of DNA 3′-blocks on plant development using the zinc finger DNA 3'-phosphoesterase ( zdp ) AP endonuclease2 ( ape2 ) double mutant, in which 3′-blocking residues are poorly repaired. The accumulation of DNA 3′-blocked triggered diverse developmental defects that were dependent on the ATM and RAD3-related (ATR)-suppressor of gamma response 1 (SOG1) signaling module. SOG1 mutation rescued the developmental defects of zdp ape2 leaves by preventing cell endoreplication and promoting cell proliferation. However, SOG1 mutation caused intensive meristematic cell death in the radicle of zdp ape2 following germination, resulting in rapid termination of radicle growth. Notably, mutating FORMAMIDOPYRIMIDINE DNA GLYCOSYLASE ( FPG ) in zdp ape2 sog1 partially recovered its radicle growth, demonstrating that DNA 3′-blocks generated by FPG caused the meristematic defects. Surprisingly, despite lacking a functional radicle, zdp ape2 sog1 mutants compensated the lack of root growth by generating anchor roots having low levels of DNA damage response. Our results reveal dual roles of SOG1 in regulating root establishment when seeds germinate with excess DNA 3′-blocks. Abstract : The ATR-SOG1 signaling module mediates checkpoint responses to 3'-blocked DNA repair intermediates and salvages the mitotic competency of the embryonic root meristem.